No rubber dam, no endo: a literature review: Tidak ada rubber dam, tidak boleh endodontik - Juni Jekti Nugroho; Serlita Wahyu Utami (Makassar Dental Journal PDGI Makassar, 2020)
Introduction: Rubber dam is the standard of the American Association of Endodontists (AAE) when dentist carrying out endodontic treatment. Dentists who do not use rubber dam indicates that they do not understand cross infection, the need to protect patients from aspiration or ingestion of instruments, the protection provided by the dentist from aerosols and the success rate that decreases when strict asepsis is not performed. In endodontic treatment a fast, simple and effective method of the rubber dam application has been developed. Conclusion: Using rubber dam improves the safety of patients and convenience for dentists during endodontic treatment so it can increase the prognosis in treated teeth.